1981
DOI: 10.1007/bf00233593
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepithelial bodies in the lung of the tree frog, Hyla arborea L.

Abstract: The endocrine-like cells (ELC), which together with nerve endings form the neuroepithelial bodies, are located on primary and secondary septa in the non-ciliated epithelium of the lung of Hyla arborea. ELC protrude markedly toward the lumen of the lung and are surrounded by pneumocytes, which separate ELC from the lumen by thin cytoplasmic processes. ELC possess a light cytoplasm containing two types of granules: (i) numerous small granules, 50-110 nm in diameter, and (ii) single large granules, 290-860 nm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Neuroendocrine cells have been identified in the lungs of birds (Cook & King 1969;Walsh & McLelland 1974;Wasano & Yamamoto 1979) and reptiles (Scheuermann et al 1983;Pastor et al 1987Pastor et al , 1988Pastor et al , 1989. In amphibian lungs they occur both individually or as neuroepithelial bodies (Goniakowska-Witalinska 1980, 1981Cutz et al 1986;Goniakowska-Witalinska & Cutz 1990;Goniakowska-Witalinska et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroendocrine cells have been identified in the lungs of birds (Cook & King 1969;Walsh & McLelland 1974;Wasano & Yamamoto 1979) and reptiles (Scheuermann et al 1983;Pastor et al 1987Pastor et al , 1988Pastor et al , 1989. In amphibian lungs they occur both individually or as neuroepithelial bodies (Goniakowska-Witalinska 1980, 1981Cutz et al 1986;Goniakowska-Witalinska & Cutz 1990;Goniakowska-Witalinska et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The investigations carried out so far point out that in amphibians the nerve endings are located in the basal part of NEB Haller, 1978, 1980;Wasano and Yamamoto, 1978;Goniakowska-Witalinska, 1981;Matsumura, 1985;Scheuermann et al, 1989;Goniakowska-Witalinska and Cutz, 1990;GoniakowskaWitalinska et al, 1990). The present study revealed a morphologically atypical innervation of NEB in A .…”
mentioning
confidence: 95%
“…However, both the size and electron-density of the DCVs vary greatly, not only from cell to cell, but even within the same cell (e.g. Goniakowska-Witalinska, 1981;Lauweryns et al, 1974). Based on the size and electron density of the DCVs some authors have described at least three, apparently different types of NEE cells in the fetus and the newborn infant (Hage, 1974), whereas only one type was identified in adult human lungs (Capella et al, 1978;Cutz and Orange, 1977;Hage, 1984).…”
Section: Ultrastructure Of Solitary Neuroepithelial Endocrine Cells Amentioning
confidence: 96%